DIALECT IN INTERACTION BETWEEN SELLERS AND BUYERS AT PASAR RAME MEDAN - Melina Putri; Amrin Saragih; Anni Holila Pulungan (LINGUISTICA, 2018)
The research was focused on the topic about Dialect caused by in Interaction between Sellers and Buyers at Pasar Rame Medan. This study was aimed at identify the dominantly types dialectcaused by and realize the dialect that used in interaction between sellers and buyers at Pasar Rame Medan. The source of data was taken from the conversation between sellers and buyers at Pasar Rame Medan that used dialect. The data were collected by using recording technique. Instrument for collecting the data is using tipe recording. The technique for analyzing the data is descriptive qualitative research. The result of this research was types of dialect caused by can be found are, Geographical (33,33%), Socio-Economic Status (SES) (36,66%), Age(23,33%), and Sex (6,66%).The most dominant type of dialect that used in interaction between sellers and buyers at Pasar Rame Medan is Socio-Economic Status with percentage 28.80% .Realize of the dialect that found in interaction between sellers and buyers at Pasar Rame Medan  were made possible by some factors: Phonology (pronounce, stress, tone and pitch) , lexicon and grammatical aspects. Keywords: Dialect, Phonology